(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the impact of the intervention: motivation and follow-up by health professionals in the duration and exclusivity of breastfeeding, by means of a randomized clinical trial. In the pregnancy, women they were interviewed (n = 154) and followed up until the six month after delivery. In the pregnancy, all received pamphlets and watched a video on breastfeeding promotion in the first interview, being randomly divided into groups: intervention (n = 51) and control (n = 103). The group Intervention was receive home care for up to 5 days and a telephone call back 2 and 14 weeks after delivery by health professionals. After 6 months, 124 mothers (Intervention = 50 and Control = 74) were interviewed. The mothers’ mean age was 26.5 (± 6.1) years, and the majority were non-white skin color (58.9%), lived with a partner (79%), with up to 8 years of schooling (70.2%); multiparous (64.5%); did not work (54.8%), and earned up to 2 Minimum Wages (81.4%). Most babies were male (52.4%) and born by cesarean section (61.3%). Exclusive breastfeeding rates in intervention were 84%, 82%, 54% and 34% for 5 days, 2 weeks, 14 weeks and 6 months, respectively and in control was 17.6% for 6 months. The group intervention had higher rates of exclusive breastfeeding (p = 0.03, RR 1.25) and breastfeeding (p = 0.02, RR 2.03) compared to control. The studied intervention (motivation and follow-up) promoted positive changes in the duration and exclusivity of breast feeding at 6 months of age, compared to traditional health education, and can be used in the promotion of breastfeeding practice by health services.